The Premature Obituary of Programming: Why deep learning will not replace programming. - Yellin, Daniel M. (Communications of the ACM, 2023)
The article focuses on why deep learning (DL) will not replace programming. The author examines what he calls "deep programming" (DP) and large transformer language models, explores new machine and network architectures, and discusses integrating search-based program synthesis with DP. He argues that computers will not replace coding by humans.